Sistematização de conteúdos da Educação Física para as séries iniciais - Kawashima, Larissa Beraldo; de Souza, Laura Beraldo; Ferreira, Lílian Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2009)
The school culture reveals an organization, over all in terms of the distribution of the contents throughout the different levels of education. However, the Physical Education does not have its contents systemized, that is, there are no clearly definite criteria that can assist the teacher in the curricular organization, as well as, are restricted the didactic books of reference for the area. So, the aim of this study was to try the identification of relevant contents for the teach-learning of the scholar Physical Education pertaining of 1(a) to 4(a) series, as well as, a suggestion to organize these contents in a systemize form, respecting a pedagogical sequence for the indicated series. Field research was carried out, in which was used the practical experience of two of the authors of this article, that are Physical Education teachers, throughout three years. The data were collected by descriptions and daily of field, of the positive experiences lived by the teachers.

A cultura escolar revela uma organização, sobretudo em termos da distribuição dos conteúdos ao longo dos diferentes níveis de ensino. Contudo, a Educação Física não tem seus conteúdos sistematizados, ou seja, não existem critérios claramente definidos que auxiliem os professores na organização curricular, bem como, são bastante restritos os livros didáticos para a área. Assim sendo, este estudo procurou identificar os conteúdos relevantes para o ensino-aprendizagem da Educação Física escolar de 1ª a 4ª séries, bem como, uma sugestão para organizá-los de forma sistematizada, respeitando uma seqüência pedagógica para as seriações já indicadas. Foi realizada pesquisa de campo, na qual se utilizou a experiência prática de duas das autoras do referido artigo, docentes estas que atuavam no ensino da Educação Física ao longo de três anos. Os dados foram coletados por meio das descrições, diário de campo, das experiências vivenciadas pelas professoras.
Systematization of contents of Physical Education for early series
Keywords: School; Physical Education; Contents; Systemize